Outbreak of isoniazid resistant tuberculosis in north London. Issue 4 (26th March 2004) - Ruddy, M C; Davies, A P; Yates, M D; Yates, S; Balasegaram, S; Drabu, Y; Patel, B; Lozewicz, S; Sen, S; Bahl, M; James, E; Lipman, M; et al.
Abstract : Background: A description is given of a major outbreak of isoniazid monoresistant tuberculosis (TB) chiefly in north London, including prisons. The earliest case was diagnosed in 1995 with most cases appearing after 1999. Methods: Confirmation of a local cluster of cases was confirmed by restriction fragment length polymorphism (RFLP IS6110) typing or "rapid epidemiological typing" (RAPET). Further cases were found by retrospective analysis of existing databases, prospective screening of new isolates, and targeted epidemiological case detection including questionnaire analysis. Results: By the end of 2001, 70 confirmed cases in London had been linked with a further 13 clinical cases in contacts and nine epidemiologically linked cases outside London. The epidemic curve suggests that the peak of the outbreak has not yet been reached. Cases in the outbreak largely belong to a social group of young adults of mixed ethnic backgrounds including several individuals from professional/business backgrounds. Compared with other cases of TB reported to the enhanced surveillance scheme in London during 1999–2001, the cases are more likely to be of white (26/70 (37%) v 1308/7666 (17%)) or black Caribbean ethnicity (17/70 (24%) v 312/7666 (4%)), born in the UK (41/70 (59%) v 1335/7666 (17%)), and male (52/70 (74%) v 4195/7666 (55%)). Drug misuse and/or prison detention are factors common to many cases. Conclusions: The investigation of the outbreak revealed significant problems on an individual patient and population based level including difficulties with contact tracing, compliance, and the risk of developing multidrug resistance. This incident has demonstrated the value of molecular strain typing in investigating an extensive outbreak of TB. This is the first documented outbreak involving a UK prison.